THE COMMUNICATION STRATEGIES IN FLOOD DISASTER PREPAREDNESS IN SUNGAI TABUK - Mutiani, Mutiani; Rusmaniah, Rusmaniah; Jumriani, Jumriani; Triyono, Sigit; Firdaus, Akhmad Maulana (International Conference On Social Science Education, 2024)
Communication in flood disasters is not only needed in disaster emergencies, but is also important during pre-disaster, emergency response, and post-disaster. Preparing communities in flood-prone areas must always be done. One of them is through disaster education. The purpose of this research is to describe the communication strategy in flood disaster preparedness in Sungai Tabuk. The research method used is a qualitative approach with data collection techniques used are in-depth interviews, observation, and documentation studies. The results of the research that has been conducted show the existence of interactive communication strategies in flood preparedness, including: 1) customer focus, through simple messages, 2) leadership commitment, namely proactive leadership in preparation, 3) situational awareness, public awareness of the situation, and 4) media partnership, utilizing various digital and conventional media for information dissemination. However, it was found that there is still a digital divide among the elderly community that needs to be addressed.